Antecedents of export performance: empirical evidence from Malaysian Construction Professional Consultants / Abdul Latif Mohd Som, Datuk Ir - Mohd Som, Abdul Latif (2014)
The effects of globalization have resulted in many firms exploring beyond their national boundaries in search of a better business performance. Resulting therefrom, increasing efforts have been made by researchers in the recent past in order to determine the antecedents of export venture performance of firms in addition to defining the appropriate dimensions of export performance. The objectives of this study are: (i) to explore the possible dimensions of export performance including its relationship between one dimension and another, (ii) to identify the main antecedent variable to export performance, (iii) to analyze the relationships between one antecedent variable and another, and (iv) to analyze the moderating effects of the 4 moderators on five critical links. Data were collected from 55 participating firms which were drawn from the Malaysian Construction Professional Consultants specifically those which are construction, total of 205 usable questionnaires were returned. Data analyses were conducted by a process of multivariate analysis using structural equation modelling (SEM) via AMOS (Analysis of Moment Structures) software package Version 21.0. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to validate the scales. The results of the structural modelling revealed that for the direct relationships, 13 out of 20 hypotheses tested were supported whereas the remaining 7 were rejected. Only one hypothesis on the mediating variable was supported whereas out of 20 sub-hypotheses on the 4 moderators tested, all were supported except for 2 which were rejected. The results provide evidence that management factors are important antecedent towards shaping up the necessary resources, products/services characteristics of the firm and the export market strategy of the firm. On the most crucial outcome of export financial performance, the study revealed that it is dependent upon the degree of internationalisation of the firm and the export market strategy that the firm is pursuing. Additionally, capabilities were found to have a mediating effect on the relationship between management characteristics and the degree of internationalisation. The four moderators were found to have significant effects on several relationship links. Hence, it is proven by this study that the traditional model of export performance applied to manufactured goods comprising the same variables can be applied to describe the antecedents of export performance of service firms as validated. On the relationship between the two main dimensions of export performance and export non-financial performance, it was established in this study, for the first time to the best of the researcher's knowledge, that strategic export performance is positively linked to economic export performance. This study also contributes towards empirical research in export performance in a full-service firm setting from an emerging economy and in particular within the context of Malaysia.